Virtual GIS walkthrough Innovation Center / Mohd Sufean Abu Samah - Abu Samah, Mohd Sufean (1999)
Nowadays advances in computer graphics hardware and algorithms, visualization and interactive techniques for analysis offer the components for a high integrated, efficient real-time 3d Virtual GIS. The purpose of this project is to develop a system that enables a user to engage in a virtual visit to Innovation Center in ITM Shah Alam. This is an application of the virtual GIS technology. A coloured virtual model of the building will be built by using architectural drawing and this system provides the means visualizing terrain models consisting all view of the environment. By applying the virtual GIS tools, the necessary objects would be rendered. Once built, a user be able to move freely through out the building interactively this is what is mean by walkthrough. A standard called VRML (Virtual Reality Modeling Language) and Caligari Truespace 3.0 has been developed to enable virtual reality application to be implemented on the web. Although there are limited development available in VRML, the non-internet version has advanced considerably to make this project viable. The project is still at the initial stage and need further enhancement especially to choose the right software before being shown to the public.